Effects of virtual reality guided meditation in older adults: the protocol of a pilot randomized controlled trial - Cinalioglu, Karin; Lavín, Paola; Bein, Magnus; Lesage, Myriam; Gruber, Johanna; Se, Jade; Bukhari, Syeda; Sasi, Neeti; Noble, Helen; Andree-Bruneau, Marie; Launay, Cyrille; Sanders, Justin; et al. (Frontiers in Psychology, 2023)
Background: Virtual Reality (VR) based meditation has been shown to help increase relaxation and decrease anxiety and depression in younger adults. However, this has not been studied in Randomized Controlled Trials (RCT) in the older adult population. The aim of this RCT is to assess the feasibility and acceptability of a VR-guided meditation intervention for community-dwelling older adults and its effect on stress and mental health. Methods: We will recruit 30 participants aged ≥ 60 years, whose perceived stress score (PSS) is >14 (moderate stress), and randomize them 1:1 to the intervention or control waitlist group. The intervention will involve exposure to eight 15-minute VR-guided meditation sessions distributed twice weekly for 4-weeks. Two modalities will be offered: in-home and at the hospital. Data Analysis: Baseline and post-intervention assessments will evaluate perceived stress, anxiety, depression, sleep quality, quality of life, and mindfulness skills. Analyses will employ repeated mixed design ANOVA. Qualitative analyses through semi-structured interviews and participant observation will be used to assess participants’ experiences. Study outcomes include: A) feasibility and acceptability compared to a waitlist control B) stress, using the Perceived Stress Scale (PSS); C) anxiety, and depression, using the Generalized Anxiety Disorder-7 (GAD-7) and Patient Health Questionnaire-9 (PHQ-9); D) insomnia, quality of life and mindfulness skills, using the Athens Insomnia Scale (AIS), Quality of Life Questionnaire (EQ-5D-5L) and Five Facets Mindfulness Questionnaire Short Forms (FFMQ-SF), respectively. We will also measure simulator sickness, and sense of presence using the Simulator Sickness Questionnaire (SSQ) and the Presence Questionnaire (PQ). Discussion: VR-guided meditation can be a feasible, safe, and cost-effective novel alternative intervention for improving older adults’ mental health. Clinical Trial Registration NCT05315609 at https://clinicaltrials.gov